Combining ability, heterosis and gene action for yield and its component traits incastor (Ricinus Communis L.): Combining ability, heterosis and gene action for yield and its component traits incastor (Ricinus Communis L.) - YAMANURA; P SHRUTHI; K MADHUSUDAN; R MOHAN KUMAR; A MOHAN RAO (Journal of Oilseeds Research, 2023)
An investigation on combining ability, heterosis and gene action for yield and its component traits in castor was carried out at AICRP Castor, UAS, Bangalore involving fifty hybrids developed from five pistillate lines as females and 10 testers as males. Analysis of variance revealed significant differences among parents and crosses for all yield attributing traits. The line YRCP-1 and tester RG-3160 showed significant positive effect for seed yield. The cross MCP-1×RG- 3160, expresses significant SCA effect for earliness, spike lengths, capsules on primary spike and seed yield/plant. Hybrids MCP-1 × RG-2787 (157.50 g) and DPC-22 × RG-2787 (186.77 g) involving poor performing parents produced high magnitude for seed yield/plant and yield attributing traits like 100 seed weight and oil percent (%).